Wafer-Scale Patterning of Protein Templates for Hydrogel Fabrication - Anna A. Kim (MDPI AG, 2021)
Human-induced pluripotent stem cell-derived cardiomyocytes are a potentially unlimited cell source and promising patient-specific in vitro model of cardiac diseases. Yet, these cells are limited by immaturity and population heterogeneity. Current in vitro studies aiming at better understanding of the mechanical and chemical cues in the microenvironment that drive cellular maturation involve deformable materials and precise manipulation of the microenvironment with, for example, micropatterns. Such microenvironment manipulation most often involves microfabrication protocols which are time-consuming, require cleanroom facilities and photolithography expertise. Here, we present a method to increase the scale of the fabrication pipeline, thereby enabling large-batch generation of shelf-stable microenvironment protein templates on glass chips. This decreases fabrication time and allows for more flexibility in the subsequent steps, for example, in tuning the material properties and the selection of extracellular matrix or cell proteins. Further, the fabrication of deformable hydrogels has been optimized for compatibility with these templates, in addition to the templates being able to be used to acquire protein patterns directly on the glass chips. With our approach, we have successfully controlled the shapes of cardiomyocytes seeded on Matrigel-patterned hydrogels.